Synthesis, Computational Studies, and Biological Evaluation of Chalcones as Antifungal Agents - Sharma, Jatin Kishore; Kumari, Akhlesh; Kumar, Amit; Kumar, Sushil; Verma, Shweta (Anti-Infective Agents, 2026)
Introduction/BackgroundChalcone-based compounds display potential antifungal activity. They are considered to be versatile pharmacophores that can be utilized for the designing and development of numerous bioactive lead compounds. In this work, some new chalcone derivatives were synthesized, which are expected to possess antifungal activity, making them potentially useful for treating fungal infections.ObjectiveThe rate at which fungi develop resistance to antifungals is outpacing the discovery of new antifungal classes. Developing new compounds with the same behavior but improved pharmacological action has proven to be a significant challenge for scientists. Therefore, discovering novel drugs is crucial for combating health problems and enhancing the quality of human life. For this reason, in this study, we synthesized new chalcones and evaluated their antifungal activity.MethodsIn the initial phase, in silico studies were employed to predict the physicochemical properties and biological activities of chalcone derivatives. A new series of chalcones was synthesized using synthetic methodologies, and characterization techniques, such as spectroscopy and chromatography, were employed to confirm the identity and purity of the compounds. The antifungal potential of chalcones was checked by the zone inhibition method (Kirby-Bauer method) using Candida albicans and Candida parapsilosis strains. Subsequently, molecular docking against fungal targets was performed to elucidate the binding interactions, providing valuable insights into the structure-activity relationship, and cytotoxicity studies were performed to assess the potential toxicity of these compounds.Results and DiscussionThe target compounds (Ca-Ce) were successfully synthesized and characterized by spectroscopic and analytical methods. The findings from the computational properties and activity against fungal stains like Candida albicans and Candida parapsilosis revealed that the newly synthesized chalcones exhibit significant antifungal potential.ConclusionThe newly synthesized chalcones, especially Cc and Ce, exhibited antifungal activity nearly equivalent to that of standard drugs.
Keywords: physicochemical parameter